FAKTOR-FAKTOR YANG MEMPENGARUHI INDEKS HARGA SAHAM PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX - Taufiq, Rahmat; Wahidahwati, Wahidahwati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to find out the influence factorof the stock price index which consist of fundamental factor and technical factor. Fundamental factor of this research are EPS, PER, ROA, DER, DPR, PBV, and NPM. Meanwhile, the technical factor of this research is volume trading to the stock price index. The object of this research is manufacturing company which is listed in Jakarta Islamic Index (JII). The data of this research is obtained from the annual financial statement at IDX in 2011-2014. The sample of this research is selected by using purposive sampling technique so that it obtains 49 companies which aremeet the criteria. From the result of analysis found that EPS and ROA have positive influence to the Stock Price Index (IHS), and volume trading have negative influence to the Stock Price Index (IHS), meanwhile PER, DER, DPR, NPM and PBV does not have any influence to the Stock Price Index (IHS). The prediction ability of those eight variables to the Stock Price Index (IHS) is 70,1%, meanwhile the rest is 29,9% it has been explained by other variable which is not including to this research.Keywords: factor fundamental, factor technical, stock price index